2003
DOI: 10.1089/107555303322524562
|View full text |Cite
|
Sign up to set email alerts
|

Potentized Mercuric chloride and Nux vomica Facilitate Water Permeability in Erythrocytes of a Fresh-Water CatfishClarius batrachusUnder Acute Ethanol Intoxication

Abstract: Because water channel proteins or aquaporins are mainly responsible for water transport through the plasma membrane of RBCs, it is thought that potentized drugs interact with these proteins, thereby facilitating water influx in the cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…We had observed earlier that Nux vomica 30 and Mercury chloride 30 interfered with the transport of water through the plasma membrane of erythrocytes in fresh water cat fish. We proposed that homeopathic potencies acted on water channel proteins of the membrane and produced that effect [9]. After entering the muscle cell, T. spiralis induces significant phenotypic changes in the cell which then re-enter the cell cycle and replicate their DNA [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had observed earlier that Nux vomica 30 and Mercury chloride 30 interfered with the transport of water through the plasma membrane of erythrocytes in fresh water cat fish. We proposed that homeopathic potencies acted on water channel proteins of the membrane and produced that effect [9]. After entering the muscle cell, T. spiralis induces significant phenotypic changes in the cell which then re-enter the cell cycle and replicate their DNA [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of chopped muscles of each group of mice was weighed, kept in a BOD incubator at 90 °C for 12 h to remove water and then weighed again. Total water content in the muscles was assessed by measuring the difference between fresh weight and dry weight of the tissues [9,13,14]. The adult worms live in the intestine.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts of strychnous nux-vomica has been found to reduce voluntary alcohol intake in rats [17]. A possible proposed mechanism of action is that the drug interacts with membrane aquaporins facilitating water influx into cells [18].…”
Section: Whole Medical Systemsmentioning
confidence: 99%
“…Studies on biological markers of alcoholism have found alcoholics and sons of alcoholics to have EEG wave patterns in the fast alpha (9-12 Hz) and beta (12)(13)(14)(15)(16)(17)(18)(19)(20) Hz) range [81][82][83]. Biofeedback aims at the patient learning to convert her/his brain wave activity from the alpha to theta range.…”
Section: Electroencephalogram Biofeedbackmentioning
confidence: 99%